Clinical characteristics and social determinants of health associated with 30-day hospital readmissions of patients with COVID-19. (1st June 2022) - Wiley, Zanthia; Kulshreshtha, Ambar; Li, Dong; Kubes, Julianne; Kandiah, Sheetal; Leung, Serena; Kobaidze, Ketino; Shin, Sangmin Ryan; Moanna, Abeer; Perkins, Jonathan; Hogan, Matthew; Sims, Kanika M; et al.
Abstract : COVID-19 readmissions are associated with increased patient mortality and healthcare system strain. This retrospective cohort study of PCR-confirmed COVID-19 positive adults (> 18 years) hospitalized and readmitted within 30 days of discharge from index admission was performed at eight Atlanta hospitals from March to December 2020. The objective was to describe COVID-19 patient-level demographics and clinical characteristics, and community-level social determinants of health (SDoH) that contribute to 30-day readmissions. Demographics, comorbidities, COVID-19 treatment, and discharge disposition data were extracted from the index admission. ZIP codes were linked to a demographic/lifestyle database interpolating to community-level SDoH. Of 7155 patients with COVID-19, 463 (6.5%) had 30-day, unplanned, all-cause hospital readmissions. Statistically significant differences were not found in readmissions stratified by age, sex, race, or ethnicity. Patients with a high-risk Charlson Comorbidity Index had higher odds of readmission (OR 4.8 (95% CI: 2.1 to 11.0)). Remdesivir treatment and intensive care unit (ICU) care were associated with lower odds of readmission (OR 0.5 (95% CI: 0.4 to 0.8) and OR 0.5 (95% CI: 0.4 to 0.7), respectively). Patients residing in communities with larger average household size were less likely to be readmitted (OR 0.7 (95% CI: 0.5 to 0.9). In this cohort, patients who received remdesivir, were cared for in an ICU, and resided in ZIP codes with higher proportions of residents with increased social support had lower odds of readmission. These patient-level factors and community-level SDoH may be used to identify patients with COVID-19 who are at increased risk of readmission.